PENGARUH PENERAPAN LKS BERMUATAN NILAI-NILAI KARAKTER DALAM STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI IPA SMA N 1 KOTO XI TARUSAN - Tiara Dela Sari (PILLAR OF PHYSICS EDUCATION, 2014)
The physics student learning outcomes is not optimal, caused LKS in schools not give meaning to students. LKS that make students understand material is LKS contain character values. This study aimed to examine effect application of LKS contain character values ​​in Contextual Teaching And Learning (CTL) learning strategies on elasticity and simple harmonic motion of students' physics learning outcomes class XI Science SMAN 1 Tarusan Koto XI. The experimental type is quasi-experimental with randomized only control group design. The population is class XI Science SMAN 1 Koto XI Tarusan in academic year 2013/2014. The sampling technique is purposive sampling with class sample class XI Science 2 and class XI Science 5. The research instrument use test for cognitive, observation format for affective, the values ​​of character and psychomotor. Analysis using t-test at the 0.05 significance level for all three domains. The results experimental is come from each domains to acceptance criteria of Ho - t (1-1/2 α ) < t < t (1-1/2 α ), ttable is 2.00 with ​​for each domain. The results calculations t count on the cognitive is 2.188; t count on the affective is 4.948; t count on psychomotor is 2.631. t count value for all domains is in region of rejection Ho and Hi received. So, there is effect of the application LKS contain character values ​​in Contextual Teaching And Learning (CTL) learning strategies of students' physics learning outcomes class XI Science SMAN 1 Koto XI Tarusan at 0.95 confidence level